Alliffa HUBUNGAN UPAH DAN TINGKAT KESEJAHTERAAN PEMAIN BOLA VOLI DALAM MENGIKUTI PERTANDINGAN ANTAR KAMPUNG (TARKAM) DI KOTA SEMARANG (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the needs and welfare level of volleyball players in participating in inter-village matches. This study uses a mixed method research, namely in conducting research the researcher uses a combination of quantitative methods and qualitative methods. Methods of data collection using questionnaires, observation, documentation, and interviews. The research instrument used a questionnaire (questionnaire). The data analysis technique uses quantitative descriptive analysis techniques which are expressed in the distribution of scores and percentages to predetermined rating scale categories. The results showed that according to the sub-indicators of physiological needs, security needs, ownership needs, reward needs, self-activation needs, the welfare level of volleyball players in participating in inter-village competitions (tarkam) in Semarang City, the majority are in the high category. This shows that volleyball players who participate in inter-village competitions have been fulfilled from all sub indicators ranging from athlete's physiology, safety when competing, having good needs, awards awarded according to the efforts of athletes, and athlete's self-actualization